Literature Review: Confidentiality Issues Between Guidance and Counceling Teachers and Colleagues - Fauziyah Putri Salsabilla (Study Program Guidance and Counseling, Univesitas Pendidik, 2023)
Confidentiality in guidance and counseling plays an important role in professional ethics. However, collaboration between counseling teachers and colleagues often raises confidentiality issues. This literature review aims to collect data on confidentiality issues between guidance and counseling teachers and colleagues. The research was conducted through secondary data analysis from relevant literature sources, rather than direct observation. Based on the research conducted, there are at least four issues related to confidentiality between counseling teachers and their colleagues, such as student confidentiality, limits to collaboration, professional collaboration, and ethics in communication. With these issues, it is expected that counseling teachers and peers can focus on the applicable code of ethics, receive ethics training, have frequent meetings, and maintain open communication to overcome confidentiality issues.